انتشار الإسلام في المدينة "يثرب" قبل الهجرة النبوية 11 بعثة = 620 م. - 13 بعثة = 622 م. - الحسن، أحمد سعود أحمد (جامعة الإسكندرية - كلية الأداب, 2016)
يعتبر انتشار الإسلام في المدينة خلال السنتين من 11 بعثة / 620 م- 13 بعثة/ 622 م من الأحداث المهمة الكبرى في السيرة النبوية، حيث يعد هو الأساس الذي اعتمد عليه النبي صلى الله عليه وسلم في ترك مكة المكرمة والهجرة إلى المدينة ثم على جهود الأنصار من قبيلتي الأوس والخزرج "أهل المدينة" اعتمد النبي صلى الله عليه وسلم بشكل أساسي في تكوين الدولة الإسلامية الأولى وحمايتها من قريش والقبائل الوثنية واليهود وغيرهم من أعداء الدولة الناشئة، وفي الوقت نفسه تعتبر المدينة هي المركز الذي انطلق منه النبي صلى الله عليه وسلم في بسط سيطرة دولة الإسلام في المدينة على جميع أنحاء الجزيرة العربية، ونشر الإسلام فيها ما يعني أن جميع ما ترتب من إنجازات كبرى في السيرة النبوية الأصل فيه يرجع أساساً إلى انتشار الإسلام بين أهل المدينة أولاً. إن مسألة انتشار الإسلام بين قبيلتي الأوس والخزرج دون غيرها من القبائل تستدعي النظر في الأسباب الحقيقية التي تميزوا بها فدخلوا في الإسلام دون غيرهم، فقريش التي اجتهد النبي صلى الله عليه وسلم في دعوتها عشر سنوات رفضت الإسلام والقبائل العربية الأخرى التي كان يدعوها صلى الله عليه وسلم في مواسم الحج والأسواق لم تسلم أيضا، مما يقتضي البحث عن أسباب هذا التميز. فهذه الدراسة محاولة لتفسير هذه الإشكالية باستقصاء العوامل المختلفة التي أدت إلى تحول سكان المدينة "قبيلتي الأوس والخزرج" من الوثنية إلى الإسلام بينما غيرهما من القبائل لم يفعل ذلك.
Actually, spread of Islam in Madina during the two years from 11 A. H/ 620 AD till 13 A. H/622 AD is considered among the most important events that occurred in the life of the Prophet Muhammad (Peace be upon him) as it represents the basic and foundation adopted by the Prophet Muhammad (Peace be upon him) in leaving Mecca and perform an immigration to Madina, as well as the efforts exerted by supporters of the tribes of Aws and Khazraj “People of Madina”. However, the Prophet Muhammad (Peace be upon him) basically depended on the same regulations in the formation of the first Islamic State and provide it with the required protection against people of Quraysh, Pagan tribes, Jews, and other enemies of the newly established State. Meanwhile, Madina was the center where the Prophet Muhammad (Peace be upon him) launched to spread Islam all over the Arabian Peninsula. Therefore, all achievements that have been largely established in the life of the Prophet Muhammad (Peace be upon him) are primarily associated with spread of Islam among people of Madina. In the same context, an issue of spreading Islam among the two tribes of Aws and Khazraj regardless the others is a matter requires an investigation about the reasons behind. It’s known that they embraced the Islamic religion regardless the others as people of Quraysh refused it, although the Prophet Muhammad (Peace be upon him) strived to inform them about teachings of Islamic religion for a period estimated ten years. In addition, Islam was refused also by other Arabian tribes which have been invited by the Prophet Muhammad (Peace be upon him) to convert into during several seasons of pilgrimage. Consequently, this issue requires recognizing the reasons behind such discrimination. Finally, this study is an attempt to interpret and analyze such problematic issue by investigating different factors which resulted in converting people of Madina from idolatry into Islam, nevertheless, other existing tribes have not embraced Islam.
Keywords: التاريخ الإسلامي -- الدعوة الإسلامية -- المدينة المنورة -- السيرة النبوية